Digital village system transformation to increase the potential of Sidemen Village Karangasem Bali - Ni Luh Ayu Kartika Yuniastari Sarja; Ida Ayu Gde Suwiprabayanti Putra; Nyoman Ayu Nila Dewi (Bulletin of Social Informatics Theory and Application, 2024)
Sidemen Village is one of the villages in Karangasem Regency. The most famous products from Sidemen Village are songket cloth and lontar comics. Seeing the potential that exists in Sidemen Village, it is necessary to develop a Digital Village in Sidemen Village, Karangasem. Digital villages will help improve communication between village officials and fellow village officials and with village residents. The research method uses the SDLC method which includes planning, analysis, design, implementation, and testing stages. At the planning stage, data is collected which will later be used in the analysis process. At the analysis stage, an analysis of functional requirements is carried out as a basis for the Digital Village website design process. At the design stage, the design of the Digital Village website is carried out in the form of database design to show what data is processed on the website. At the implementation stage, implementation is carried out in the form of website page implementation. At testing stage, data is collected through questionnaires and testing using the TAM method using the SPSS application. The system produces 10 features on the website in the form of: Admin Login, Village Resident Login, Village Information, Village Information Dashboard, Land Dashboard, Correspondence Dashboard, Assistance Dashboard, Financial Dashboard, Village Resident Dashboard. Based on the results of hypothesis testing from the proposed model, it is known that there is only 1 hypothesis that is accepted, namely the influence of PEOU on ATU, which means that the belief that the application can be easily understood and used has an influence on acceptance or rejection of the use of the application as a result when someone uses an application in a particular job or activity.